2015
DOI: 10.1039/c5cp02983j
|View full text |Cite
|
Sign up to set email alerts
|

A cocatalyst-free Eosin Y-sensitized p-type of Co3O4 quantum dot for highly efficient and stable visible-light-driven water reduction and hydrogen production

Abstract: Owing to the effect of energy band bending, p-type Co3O4 quantum dots sensitized by Eosin Y showed a high and stable photocatalytic activity (∼13,440 μmol h(-1) g(-1)(cat)) for water reduction and hydrogen production under visible-light irradiation without any cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…1b, CdS exhibits a broad emission centered at 545 nm, which is attributed to the irradiative bandtransition recombination of photogenerated electrons and holes. [36] When Co was added, the band-transition emission of CdS was quenched dramatically and slightly redshifted from 545 nm to 550 nm, which is likely due to the close interaction between Co and CdS, [37][38][39] Co adsorption, which is in good agreement with the PL results.…”
Section: Interaction Between Cds and Co Coenzymesupporting
confidence: 64%
“…1b, CdS exhibits a broad emission centered at 545 nm, which is attributed to the irradiative bandtransition recombination of photogenerated electrons and holes. [36] When Co was added, the band-transition emission of CdS was quenched dramatically and slightly redshifted from 545 nm to 550 nm, which is likely due to the close interaction between Co and CdS, [37][38][39] Co adsorption, which is in good agreement with the PL results.…”
Section: Interaction Between Cds and Co Coenzymesupporting
confidence: 64%
“…It is noted that the work function is closer to the VBM of WSe 2 (−5.35 eV), which indicates that the pristine WSe 2 has inherent p‐type characteristics. The flat band potential of the EY layer is ≈−5.04 eV . In EY‐WSe 2 heterolayers, electron transfer will take place from WSe 2 to low‐lying EY to compensate the energy level difference, and their work function should be between the levels of WSe 2 and EY.…”
Section: Results and Disccussionmentioning
confidence: 99%
“…EY's lowest unoccupied molecular orbital (LUMO) level is positioned lower than the CBM of 6L WSe 2 , and its highest occupied molecular orbital (HOMO) level is lower than the VBM of 1L WSe 2 , forming a type II alignment . Additionally, EY is a water‐soluble dye molecule and can provide a p‐doping on WSe 2 . In a previous report, we found that not only organic dopants, but also solvents where dopant molecules are dispersed can contribute to interlayer charge transfer to/from 2D TMDC layers, depending on the relative electronegativity .…”
Section: Introductionmentioning
confidence: 99%
“…ii) The excited electrons at TiO 2 may suppress to transfer to CFCO by widening of bandgap energy of CFCO by decreasing of particle size to 5 nm, i.e., quantum confinement effect. Some researchers reported that bandgap energies of simple oxides such as Co 3 O 4 [ 38,39 ] and Fe 2 O 3 [ 40 ] became larger with decreasing the particle size to 3–4 nm. In our case (Figure S8, Supporting Information), CFCO/TiO 2 prepared by the RM method with R w = 3 showed specific visible light absorption at less than 900 nm (the sample color is yellowish), even though the electrons and holes excited by such visible light were not used to oxygen photoevolution reaction (Figure S9, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%